2021
DOI: 10.1016/j.isci.2021.102132
|View full text |Cite
|
Sign up to set email alerts
|

The neural correlates of ongoing conscious thought

Abstract: Summary A core goal in cognitive neuroscience is identifying the physical substrates of the patterns of thought that occupy our daily lives. Contemporary views suggest that the landscape of ongoing experience is heterogeneous and can be influenced by features of both the person and the context. This perspective piece considers recent work that explicitly accounts for both the heterogeneity of the experience and context dependence of patterns of ongoing thought. These studies reveal that systems link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 106 publications
5
99
0
1
Order By: Relevance
“…Additionally, it has been shown that the DMN is sensitive to the level of vivid detail in experience during spontaneous cognition and task contexts ( Sormaz et al. 2018 ; Smallwood et al. 2021 ).…”
Section: Principle 4: Spontaneous Perception Relies On Associative Processingmentioning
confidence: 99%
“…Additionally, it has been shown that the DMN is sensitive to the level of vivid detail in experience during spontaneous cognition and task contexts ( Sormaz et al. 2018 ; Smallwood et al. 2021 ).…”
Section: Principle 4: Spontaneous Perception Relies On Associative Processingmentioning
confidence: 99%
“…Dimension reduction techniques can then be applied to use covariation in the responses to different questions to identify "patterns of thought" (37,39). Previous studies have used MDES to identify common patterns of ongoing thought, varying in both form and content, often with distinct neural correlates (28,37,(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, sensory/motor systems as well as unimodal association cortices are involved in operations related to perceiving and acting in the outside world. These systems are differentiated from transmodal systems that are less tied to a specific modality, and are increasingly engaged in abstract and self-generated cognition together with communication with the “internal milieu” 14 . These functional differences are reflected in well-established differences in the microstructure of sensory/motor and transmodal cortex.…”
Section: Introductionmentioning
confidence: 99%